Radial Electric Field and Transport near the Rational Surface - Pysarevsky, A. S.; Kozak, I. A.; Chernyshov, N. N. (ХНУРЭ, 2010)
The structure of the radial electric field and heat transport at the magnetic island in the Large Helical Device is investigated by measuring the radial profile of poloidal flow with charge exchange spectroscopy. The convective poloidal flow inside the island is observed when the n/m=l/l external perturbation field becomes large enough to increase the magnetic island width above a critical value (15-20% of minor radius) in LHD. This convective poloidal flow results in a non-flat space potential inside the magnetic island. The sign of the curvature of the space potential depends on the radial electric field at the boundary of the magnetic island. The heat transport inside the magnetic island is studied with a cold pulse propagation technique. The experimental results show the existence of the radial electric field shear at the boundary of the magnetic island and a reduction of heat transport inside the magnetic island
Keywords: radial electric field; magnetic island